Differentiated Learning Activities: How Does Its Impact on Students' Literacy? - Nirmala, Sri Dewi; Firdaus, Fery Muhamad; Ramdhani, Sendi; Hidayat, Andi Reza; Razali, Fazilah binti (Jurnal Prima Edukasia, 2025)
Literacy skills are one of the 21st-century abilities which have an essential function in preparing students to face various global demands and challenges characterized by advances in technology and information, which are developing very rapidly and affecting all areas of human life. However, the literacy skills of elementary school students in Indonesia were still in the low category. This research aims to analyze the impact and activities of differentiated learning on elementary school students' literacy abilities. This research used mixed methods. The research design used was a sequential explanatory design. This design was implemented by collecting and analyzing quantitative data through survey techniques and then collecting and analyzing qualitative data through observation and in-depth interview techniques. The data analysis technique used in this research involved statistical techniques for quantitative data, while for qualitative data used three steps namely a) selecting and grouping, b) presenting, and c) concluding the data. The research results showed that differentiated learning activities significantly affect elementary school students' literacy skills. This approach allows learning activities relevant to student's needs and interests, thereby creating a more optimal learning environment and supporting the development of literacy skills at the elementary school level.